Optimalisasi peran anggota PKK dan dukungan keluarga sebagai upaya meningkatkan kesadaran manajemen diri pasien diabetes melitus - Sastra, Lenni; Yusriana, Yusriana; Kasmita, Kasmita (JOURNAL of Public Health Concerns, 2025)
Background: Diabetes mellitus (DM) is a chronic disease that requires optimal self-management to prevent complications. Family and community support play a crucial role in successful self-management in DM patients. Internal factors such as knowledge, motivation, and self-efficacy play a crucial role in shaping self-management behaviors in DM patients. Community-based programs that involve social support can improve the physical and mental quality of life of DM patients, especially in communities with high social vulnerability. This emphasizes the crucial role of support from the social and community environment. Purpose: To improve the capacity of the Family Empowerment and Welfare Movement Team and the families of DM patients as an effort to raise awareness of DM patients' self-management skills. Method: The activity was carried out in July–September 2025 in Koto Pulai Village, Padang City. Participants consisted of 10 Family Empowerment and Welfare members and 16 families of DM patients, with education, training, and mentoring methods, including program socialization, DM education, training in making healthy food preparations, independent health checks, physical exercise, and implementation of training results. Evaluation was carried out using a questionnaire to assess the increase in knowledge, skills, and active roles of participants, both Family Empowerment and Welfare members and families of DM patients. Results: Obtaining data that the average knowledge score of Family Empowerment and Welfare members about Diabetes Mellitus (DM) and self-management of DM patients before the activity was 14.20 and after the activity increased to 20.90 with a p-value of 0.001 (<0.005). Meanwhile, the average knowledge score of DM patients' families before the activity was 11.13 and after the activity increased to 16.81 with a p-value of 0.001 (<0.005). Based on the evaluation, it also showed that most of the mentoring roles of Family Empowerment and Welfare members before the activity were in the inactive category, namely 8 people (80.0%) and after the activity, the mentoring role of all Family Empowerment and Welfare members was in the active category, namely 10 people (100.0%) with pValue = 0.003. Meanwhile, the role of patient family support before the activity in the inactive category was 8 people (50.0%) and the less active category was 8 people (50.0%), while the role of patient family support after the activity in the inactive category was 5 people (31.0%), the less active category was 4 people (25.0%) and the active category was 7 people (44.0%). Conclusion: Direct education and training for Family Welfare Movement members and patients' families were highly effective in increasing their knowledge and active role in supporting diabetes patients. This increased support and knowledge also positively contributed to increasing awareness among diabetes patients about developing self-management patterns. Suggestion: Community Health Centers and local governments are expected to continue education and training programs for Family Empowerment and Welfare cadres, and families of diabetes patients on an ongoing basis, accompanied by regular monitoring and evaluation to ensure ongoing support. Family Empowerment and Welfare administrators should form support groups and hold regular meetings or home visits, while patients' families are expected to actively participate in diet management, physical activity, and blood glucose monitoring. Keywords: Community empowerment; Diabetes mellitus patients; Family support; Self-management Pendahuluan: Diabetes melitus (DM) merupakan penyakit kronis yang memerlukan manajemen diri optimal untuk mencegah komplikasi. Dukungan keluarga dan komunitas berperan penting dalam keberhasilan manajemen diri pasien DM. Faktor internal seperti pengetahuan, motivasi, dan self-efficacy berperan penting dalam pembentukan perilaku manajemen diri pasien DM. Program berbasis masyarakat yang melibatkan dukungan sosial mampu meningkatkan kualitas hidup fisik dan mental pasien DM, terutama di komunitas dengan kerentanan sosial tinggi. Ini menekankan bahwa dukungan dari lingkungan sosial & komunitas mempunyai peranan yang sangat penting. Tujuan: Untuk meningkatkan kemampuan Tim Penggerak Pemberdayaan dan Kesejahteraan Keluarga (PKK) dan keluarga pasien DM sebagai upaya meningkatkan kesadaran pasien DM dalam manajemen diri. Metode: Kegiatan dilaksanakan pada Juli–September 2025 di Kelurahan Koto Pulai, Kota Padang. Peserta kegiatan terdiri atas 10 anggota PKK dan 16 keluarga pasien DM, dengan metode edukasi, pelatihan, dan pendampingan, meliputi sosialisasi program, edukasi DM, pelatihan pembuatan olahan makanan sehat, pemeriksaan kesehatan mandiri, latihan fisik, serta implementasi hasil pelatihan. Evaluasi dilakukan dengan lembar kuesioner untuk menilai peningkatan pengetahuan, keterampilan, dan peran aktif peserta, baik anggota PKK maupun keluarga pasien DM. Hasil: Mendapatkan data bahwa rata-rata skor pengetahuan anggota PKK tentang Diabetes Melitus (DM) dan manajemen diri pasien DM sebelum kegiatan adalah 14.20 dan setelah kegiatan meningkat menjadi 20.90 dengan nilai p-value 0.001 (<0.005). Sedangkan, rata-rata skor pengetahuan keluarga pasien DM sebelum kegiatan adalah 11.13 dan setelah kegiatan meningkat menjadi 16.81 dengan p-value 0.001 (<0.005). Berdasarkan evaluasi juga menunjukkan bahwa sebagian besar peran pendampingan anggota PKK sebelum kegiatan adalah dalam kategori tidak aktif yaitu sebanyak 8 orang (80.0%) dan setelah kegiatan, peran pendampingan dari seluruh anggota PKK dalam kategori aktif yaitu sebanyak 10 orang (100.0%) dengan pValue=0.003. Sedangkan peran pendampingan keluarga pasien sebelum kegiatan dalam kategori tidak aktif sebanyak 8 orang (50.0%) dan kategori kurang aktif sebanyak 8 orang (50.0%), sedangkan peran pendampingan keluarga pasien sesudah kegiatan dalam kategori tidak aktif sebanyak 5 orang (31.0%), kategori kurang aktif sebanyak 4 orang (25.0%) dan kategori aktif sebanyak 7 orang (44.0%). Simpulan: Kegiatan edukasi dan pelatihan langsung kepada anggota PKK dan keluarga pasien sangat efektif dalam meningkatkan pengetahuan dan aktivitas perannya dalam pendampingan pada pasien DM. Dengan meningkatnya peran pendampingan dan tingkat pengetahuan ini juga memberikan kontribusi positif terhadap kesadaran dari pasien DM dalam membentuk pola manajemen diri. Saran: Diharapkan kepada Puskesmas dan pemerintah setempat untuk melanjutkan program edukasi dan pelatihan kader PKK serta keluarga pasien DM secara berkesinambungan, disertai monitoring dan evaluasi rutin agar pendampingan dapat berkelanjutan. Pengurus PKK perlu membentuk kelompok pendamping dan mengadakan pertemuan atau kunjungan rumah secara teratur, sementara keluarga pasien diharapkan aktif dalam pengaturan diet, aktivitas fisik, dan pemantauan glukosa darah.